Pelatihan Digital Marketing Bagi Kelompok Usaha Mikro, Kecil, Dan Menengah (UMKM) Di Kelurahan Serua, Bojongsari, Depok - Dini Putri Saraswati; Shanti Darmastuti; Mansur Juned; Pramudya Raharjo; Shan Adam Ghoffar; Andrew Matthew Sianturi (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The digital era has brought changes in various sectors, including Micro, Small and Medium Enterprises (MSMEs), especially since the COVID-19 pandemic broke out throughout the world. The use of information and communication technology is an opportunity for MSMEs to market their products more efficiently. However, the limited knowledge of MSME actors is an obstacle. Serua Village, Bojongsari, Depok is also one of those with potential MSME groups but is hampered by the digital technology operating capabilities of the actors. Therefore, community service activities were carried out regarding digital marketing training for MSMEs in Serua Village, Bojongsari, Depok. From the results of the pre-test and post-test, progress was obtained from the participants, where participants understood the meaning of digital marketing and had tried to practice using digital platforms such as e-commerce.